2006
DOI: 10.1002/bdrb.20072
|View full text |Cite
|
Sign up to set email alerts
|

Japanese medaka (Oryzias latipes): developmental model for the study of alcohol teratology

Abstract: BACKGROUND: Animal models are necessary to investigate the mechanism of alcohol-induced birth defects. We have used Japanese medaka (Oryzias latipes) as a non-mammalian model to elucidate the molecular mechanism(s) of ethanol teratogenesis. METHODS: Medaka eggs, within 1 hr post-fertilization (hpf) were exposed to waterborne ethanol (0-1000 mM) in hatching solution for 48 hr. Embryo development was observed daily until 10 days post-fertilization (dpf). The concentration of embryonic ethanol was determined enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 54 publications
1
34
1
Order By: Relevance
“…Further analysis of Adh and Aldh mRNAs also indicates that embryos at early stages of development are more sensitive to ethanol than the embryos at late stages ( Figure 5 and Figure 6). Our previous studies showed that exposure to ethanol disrupted the circulation status of the embryos in a dose-dependent manner (Wang et al, 2006). Other morphological parameters like craniofacial, cardiovascular and skeletal deformities by ethanol were also found to be dose-specific in medaka (Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Further analysis of Adh and Aldh mRNAs also indicates that embryos at early stages of development are more sensitive to ethanol than the embryos at late stages ( Figure 5 and Figure 6). Our previous studies showed that exposure to ethanol disrupted the circulation status of the embryos in a dose-dependent manner (Wang et al, 2006). Other morphological parameters like craniofacial, cardiovascular and skeletal deformities by ethanol were also found to be dose-specific in medaka (Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…Our previous studies showed that exposure to ethanol disrupted the circulation status of the embryos in a dose-dependent manner (Wang et al, 2006). Other morphological parameters like craniofacial, cardiovascular and skeletal deformities by ethanol were also found to be dose-specific in medaka (Wang et al, 2006). Recently, we have demonstrated that medaka embryos exposed to ethanol for 48 hpf have reduced cellular macromolecular constituents (Protein, RNA and DNA) which might have a direct effect on the embryonic growth during morphogenesis (Wu et al, 2008).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations